2022
DOI: 10.1186/s40885-022-00211-8
|View full text |Cite
|
Sign up to set email alerts
|

Are home-based exercises effective to reduce blood pressure in hypertensive adults? A systematic review

Abstract: Sedentarism and chronic non-communicable diseases have been a worldwide health problem that is drastically exacerbated by the COVID-19 pandemic social impacts. Home-based exercises are widely encouraged during social isolation to counterbalance the physical inactive impacts. Although, in the context of hypertension, are home-based exercises effective in blood pressure controlling? Our objective is to conduct a systematic review of high-quality controlled trials comparing the possible effects of different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Although the trial overlapped with the COVID-19 pandemic, we managed to maintain normal exercise activities, and all patients were given 12 months of exercise intervention. The results of this study are congruent with the findings of recent systematic reviews and meta-analyses on exercise reducing BP . Pan et al conducted a meta-analysis of 24 studies involving 2095 participants to evaluate the BP-lowering effect of Tai Chi among patients with hypertension.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the trial overlapped with the COVID-19 pandemic, we managed to maintain normal exercise activities, and all patients were given 12 months of exercise intervention. The results of this study are congruent with the findings of recent systematic reviews and meta-analyses on exercise reducing BP . Pan et al conducted a meta-analysis of 24 studies involving 2095 participants to evaluate the BP-lowering effect of Tai Chi among patients with hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study are congruent with the findings of recent systematic reviews and meta-analyses on exercise reducing BP. 26 , 27 , 28 Pan et al 29 conducted a meta-analysis of 24 studies involving 2095 participants to evaluate the BP-lowering effect of Tai Chi among patients with hypertension. The results showed that Tai Chi effectively improved SBP, DBP, and quality of life in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and exercise are important lifestyle factors for managing obesity and hypertension [82][83][84]. A recent network meta-analysis revealed that exercise could be as effective as pharmacologic therapy in lowering blood pressure, although the effect size of blood pressure-lowering was slightly greater with pharmacologic therapy than with exercise [84].…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Hypertension remains the leading cause of death worldwide (>10.4 million deaths per year). It may cause damage to the heart through hardening of the arteries, reducing blood flow and oxygen perfusion to the heart muscle and other tissues [5]. A sedentary lifestyle is considered the main modifiable risk factor for hypertension development [6].…”
Section: Introductionmentioning
confidence: 99%